The paradox of citizenship education in early years (and beyond): The case of education to fundamental British values. (December 2019) - Farini, Federico
In April 2015, the Early Years Inspection Handbook instructed inspectors to make a judgement on the effectiveness of leadership and management to actively promote British values in the settings. This contribution discusses the paradoxical position of fundamental British values within the cultures of education underpinning the curricular framework for early years education in England, the early years foundation stage. The introduction of education to fundamental British values as a statutory requirement for early years settings will be discussed within its historical background, linked to the arduous journey of citizenship education to its inclusion in English curricula. This historical review aims to position education to fundamental British values in early years within a much broader cultural process within education, towards the reconceptualisation of the citizenship as one of the outcomes of successful educational planning. Having positioned education to fundamental British values in early years in a powerful cultural movement within the education system, this contribution will interrogate the Early Years Inspection Handbook, early years foundation stage and other education policies via the methodology of document analysis. The aim of the analytical procedure is to explore the intersection between education to fundamental British values and the cultures of education in the early years foundation stage, to advance an assessment of the possibilities and implication of the inclusion of citizenship as an object of early years education. Such assessment suggests that the concept of child-initiated pedagogy introduced in the early years foundation stage has the potential to address children's meanings and experience of citizenship as practised and experienced, with obvious implication for the empowerment of children's agency. However, this requires the support of a pedagogy and analysis allowing children and young people to develop skills for critical thinking and political change.